Search for Lepton Flavor Violation in Υ(1S) Decays - Patra, S.; Bhardwaj, Vishal (Springer Nature, 2022)
We present a search for charged lepton flavor violation in Υ(1S)→ℓℓ′ [ℓ,ℓ′=e,μ,τ] decays using the 25 fb−1 Υ(2S) collected by the Belle detector. Using the Monte Carlo background, we estimate the upper limits of the branching fractions at 90% confidence level.
Only IISER Mohali authors are available in the record.
Keywords: Lepton Flavor; Violation